1977
DOI: 10.1002/qj.49710343602
|View full text |Cite
|
Sign up to set email alerts
|

Updating prediction models by dynamical relaxation: an examination of the technique

Abstract: SUMMARYA study is undertaken of a particular method of updating numerical prediction models. The method constrains the time development of a subset of the model fields toward a prescribed space-time estimate of those fields, while the other model variables are allowed to evolve in an explicitly unconstrained fashion. It represents an attempt to update the model by a form of dynamical relaxation.An analysis of the method is carried out in the context of the primitive equations linearized about an isothermal bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(95 citation statements)
references
References 14 publications
0
94
0
1
Order By: Relevance
“…In order to prevent this drift, we use the nudging technique (or Newtonian relaxation) developed for assimilation purposes (Davies and Turner, 1977;Schraff, 1997;Yong et al, 1998;Vidard et al, 2003) and commonly available for dynamical downscaling purposes. The nudging technique consists of relaxing the model state towards the analyses by adding a non-physical term to the model equation.…”
Section: Nudged Version Of the Qg Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to prevent this drift, we use the nudging technique (or Newtonian relaxation) developed for assimilation purposes (Davies and Turner, 1977;Schraff, 1997;Yong et al, 1998;Vidard et al, 2003) and commonly available for dynamical downscaling purposes. The nudging technique consists of relaxing the model state towards the analyses by adding a non-physical term to the model equation.…”
Section: Nudged Version Of the Qg Modelmentioning
confidence: 99%
“…Williams, 1992a, 1992b;Miguez-Macho et al, 1992;von Storch et al, 2000;Biner et al, 2002;Genthon et al, 2002;Lo et al, 2008;Salameh et al, 2010). Indiscriminate nudging was originally developed for assimilation issues (Davies and Turner, 1977;Schraff, 1997;Li et al, 1998;Vidard et al, 2003) but has become increasingly popular to drive Regional Climate Models (RCMs). The term 'indiscrimnate nudging' is thus not as commonly used as 'spectral nudging'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies have shown that RCM internal variability may be very complex and that its impact on regional climate predictions is far from negligible. One way to overcome this problem is to consider the effects on internal variability of large-scale nudging, which is a technique originally developed for assimilation issues (Davies and Turner, 1977;Schraff, 1997;Li et al, 1998;Vidar et al, 2003) but increasingly popular to drive RCMs. This technique consists of partially imposing the large scale of the driving fields on the RCM simulation with the aim of disallowing large and unrealistic departures between driving and driven fields.…”
Section: Introductionmentioning
confidence: 99%
“…Kida et al, 1991;Waldron et al, 1996;von Storch et al, 2000;Raluca Rad et al, 2008) and the indiscriminate nudging which consists in driving the RCM indiscriminately at all scales. Indiscriminate nudging is also referred to as data assimilation, dynamical relaxation, grid-point nudging or analysis nudging (Anthes, 1974;Hoke and Anthes, 1976;Davies and Turner, 1977;Stauffer et al, 1990;Lo et al, 2008;Salameh et al, 2010;Omrani et al, 2012). For indiscriminate nudging, Omrani et al (2012) showed that there exists an optimal nudging value τ closely related to the predictability time τ p τ ∼ 0.4τ p which minimizes the error both on the large and small scales.…”
Section: Introductionmentioning
confidence: 99%